Physical activity trajectories, mortality, hospitalization, and disability in the Toledo Study of Healthy Aging. Issue 4 (12th March 2020) - Sanchez‐Sanchez, Juan Luis; Izquierdo, Mikel; Carnicero‐Carreño, Jose Antonio; García‐García, Fransico José; Rodríguez‐Mañas, Leocadio
Abstract: Background: Physical activity (PA) is a recognized contributor to healthy aging. However, the majority of studies exploring its associations with adverse outcomes in cohorts of older adults use single‐time PA estimates, which do not consider its dynamic nature. The aim of the present study is to explore the presence of different PA trajectories in the Toledo Study of Healthy Aging and their association with adverse outcomes. Our hypothesis is that prospectively maintaining or increasing PA is associated with a reduced risk of adverse outcomes. Methods: We used data from 1679 participants enrolled in the Toledo Study of Healthy Aging. Trajectories based on the Physical Activity Scale for the Elderly were identified using group‐based trajectory modelling. Cox and logistic regression were used to investigate associations between PA trajectories and mortality and hospitalization, and incident and worsening disability, respectively. Mortality was ascertained by linkage to the Spanish National Death Index; disability was evaluated through the Katz Index; and hospitalization was defined as the first admission to Toledo Hospital. Models were adjusted by age, sex, smoking, Charlson Index, education, cognitive impairment, polypharmacy, and Katz Index at Wave 2. Results: We found four PA‐decreasing and one PA‐increasing trajectories: high PA‐consistent ( n  = 566), moderate PA‐mildly decreasing ( n  = 392), low PA‐increasing ( n  = 237), moderate PA‐consistent ( n  = 191), and low PA‐decreasing ( n  = 293). Belonging to the high PA‐consistent trajectory group was associated with reduced risks of mortality as compared with the low PA‐decreasing group [hazard ratio (HR) 1.68; 95% confidence interval (CI) = 1.21–2.31] and hospitalization compared with the low PA‐increasing and low PA‐decreasing trajectory groups (HR 1.24; 95% CI = 1.004–1.54 and HR 1.25; 95% CI = 1.01–1.55, respectively) and with lower rates of incident [odds ratio (OR) 3.14; 95% CI = 1.59–6.19] and worsening disability (OR 2.16; 95% CI = 1.35–3.45) in relation to the low PA‐decreasing trajectory group and at follow‐up. Increasing PA during late life (low PA‐increasing group) was associated with lower incident disability rates (OR 0.38; 95% CI = 0.19–0.82) compared with decreasing PA (low PA‐decreasing group), despite similar baseline PA. Conclusions: Our results suggest that sustaining higher PA levels during aging might lead to healthy aging, characterized by a reduction in adverse outcomes. Our study supports the need for enhancing PA participation among older populations, with the goal of reducing personal and economic burden in a worldwide aging population.